Nuclear War as It Looks - M. V. Supotnitskiy (Вестник войск РХБ защиты)
Currently, there are practically no people left who have seen the consequences of the use of nuclear weapons. This is the reason for certain frivolous statements about the advisability of using tactical nuclear weapons to solve certain tactical problems. The purpose of this work is to remind, using the example of the consequences of the atomic bombings of the cities of Hiroshima and Nagasaki, how does the nuclear war looks like in reality. Materials and Methods. Open sources from the Cold War era and more recent reviews of the consequences of the use of nuclear weapons were analyzed. The analysis was carried out from general to specific, i.e. from the understanding of physical processes underlying a nuclear explosion and determining the design of the nuclear devices, to the specific consequences of their use. Discussion. The article analyses the history of the creation of the «Gadget», «Fat Man» and «Kid» bombs, their design, preparation and the results of the use. Detailed descriptions of nuclear explosions and the consequences of their use, made both by those who used nuclear weapons and by those against whom they were used, are provided. Being imperfect in design and ineffective in using fissile matter, they showed stunning power even for the present time, destroying two densely populated cities and at least 106 thousand people at once. Real examples show the features of the destruction of engineering objects and the impact on people of the damaging factors of a nuclear explosion. Attention is drawn to the fact that the power of the bombs used was 15 and 22 kt, respectively. According to modern NATO classification, these are tactical nuclear weapons. It is designed to destroy targets in the tactical depth of enemy troop deployment (up to 300 km). The maximum power of tactical ammunition according to NATO standards is up to 100 kt. It means that the yield of the tactical ammunition used in battle will depend on the tactical mission, and not be limited to a few kilotons. Conclusions. The use of tactical nuclear weapons without escalating their power, causing large casualties among the population and the risk of being drawn into a global nuclear war is impossible. Currently, the world is oversaturated with nuclear and thermonuclear weapons. Some countries possess them secretly, others have the potential to create such weapons. Therefore, any use of nuclear weapons by anyone will lead to the lowering of the threshold of nuclear deterrence. It will become a common thing during the resolution of military conflicts.